Anaesthesia management in a child with metabolic myopathy - Ozer, A.B.; Demirel, I.; Gokdemir, T.; Erhan, O.L. (Verduci Editore, 2014)
[Abstract Not Available]
Keywords: adenosine triphosphate; carbohydrate; creatine kinase; glucose; nitrous oxide; propofol; remifentanil; rocuronium; sugammadex; thiopental; body temperature; case report; child; human; Letter; male; metabolic myopathy; muscle contraction; muscle weakness; myopathy; oxidative phosphorylation; pediatric anesthesia; preoperative care; school child